Peningkatan Prestasi Belajar Matematika pada Materi Operasi Hitung Bilangan Bulat melalui Pendekatan Latihan Keterampilan Siswa SMP - Sugiyanto Sugiyanto (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The teacher is a component that affects the creation of education in the classroom, because the teacher interacts directly with students in the process of teaching and learning activities. The process of interaction that drives learning is also called education. This research was conducted at SMP Negeri 1 Nusawungu. This type of research is Classroom Action Research conducted in two cycles, each consisting of four stages: action planning, action implementation, observation and evaluation, reflection. The purpose of this Classroom Action Research is to find out the Skills Training approach (Drill Method) that can improve mathematics learning achievement on the subject matter of Round Number Calculations in Class VII E of SMP Negeri 1 Nusawungu in the 2015/2016 Academic Year. Conclusion Based on the results of research on the Skills Training approach (Drill Method) in Mathematics subject matter, the subject of Round Number Operations in Class VII E, SMP Negeri 1 Nusawungu, 2015/2016 Academic Year, is that the Skills Training approach (Drill Method) can improve student learning achievement in class VII E Public Middle School 1 Nusawungu. Improved student achievement is indicated by the results of daily tests at each stage. The completeness rate in the initial study was 31%, cycle I was 72%, and cycle II was 91%. The average results of daily tests also increased by 65 in the initial study, 79 in the first cycle and 87 in the second cycle. So that the average increase in total learning achievement from the initial conditions to the second cycle 22.